THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION TO MENTAL HEALTH ON ADOLESCENT - Indrakila, Senyum; Cahyanto, Erindra Budi; Soetrisno, Soetrisno; Moelyo, Annang Giri; Nurinasari, Hafi (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: During the covid-19 pandemic, there are changes in living habits that must be faced by everyone, including teenagers. Adolescents in orphanages in adjustment experience stress, depression and sleep disturbances that can affect the quality of life. For this reason, progressive muscle relaxation efforts can be used as a way to improve adolescent mental health.Methods: This type of research is an analitic observational. This research was conducted at the Marhdatillah Sukoharjo Orphanage, Central Java. The subjects in this study were 42 people living in the Mardhatillah orphanage which divided into control group (27 people) and intervention group (15 people). In both the control group and the intervention group, mental health assessments were carried out twice. In the intervention group, prior to the second mental health assessment, a progressive muscle relaxation intervention was performed. Data was collected using the Strengths and Difficulties Questionnaire (SDQ) and intervention. Analyzed by independent t-test with SPSS 21.Results: The results of the independent t test were significant (p=0.042). The control group consisted of 27 subjects with a mean post-test SDQ score of 23.8 (abnormal) and post-test 13.22 (borderline). The intervention group consisted of 15 subjects with a mean SDQ score of 22.2 pre-test (abnormal) and 9.40 post-test (normal).Conclusion: Progressive muscle relaxation can improve mental health in adolescents who live in the Mardhatillah orphanage, Sukoharjo, Central Java.